“Eukairos” and “Akairos” in 2 Timothy 4:2: A Hermeneutical-Theological Study for Gospel Preachers - Aska Aprilano Pattinaja; Andris Kiamani; Chevin Papilaya (Predica Verbum: Jurnal Teologi dan Misi, 2026)
2 Timothy 4:2 emphasizes two conditions that a preacher of the gospel must face in carrying out his calling, namely "good times" (eukairos) and "bad times" (akairos). A review of the literature reveals that previous researchers have focused only on ethical, homiletic, and practical aspects without comprehensively interpreting the theological meaning of the terms εὐκαίρως (eukairos) and ἀκαιρός (akairos), resulting in a shift in meaning that has led to a partial and less contextual understanding. Therefore, this study aims to examine the lexical-theological significance of εὐκαίρως (eukairos) and ἀκαίρως (akairos) in 2 Timothy 4:2 and to analyze their implications for perseverance and continuity in gospel ministry. Through a theological hermeneutical approach, this study finds that the term eukairos refers to situations where the preaching of the gospel is openly accepted by the audience, while akairos describes a context of ministry that is full of rejection and resistance to the truth of the gospel. Four important implications for evangelists are: first, they must always be ready to serve in all circumstances; second, external situations should not change the main purpose of evangelism; third, success or rejection does not affect the spiritual reward promised by God; fourth, difficult ministry conditions actually become a vessel for God's power to be manifested tangibly. The results of this study reinforce the focus, perseverance, and integrity of missionaries in facing the dynamics of ministry at all times.